COVID-19-Triggered Acute Exacerbation of IPF, an Underdiagnosed Clinical Entity With Two-Peaked Respiratory Failure: A Case Report and Literature Review - Goto, Yosuke; Sakamoto, Koji; Fukihara, Jun; Suzuki, Atsushi; Omote, Norihito; Ando, Akira; Shindo, Yuichiro; Hashimoto, Naozumi (Frontiers in Medicine, 2022)
Because severe coronavirus disease 2019 (COVID-19) affects the respiratory system and develops into respiratory failure, patients with pre-existing chronic lung disorders, such as idiopathic pulmonary fibrosis (IPF), are thought to be at high risk of death. Patients with IPF often suffer from a lethal complication, acute exacerbation (AE), a significant part of which is assumed to be triggered by respiratory viral infection. However, whether mild to moderate COVID-19 can trigger AE in patients with IPF remains unknown. This is the case report of a 60-year-old man with a 4-year history of IPF who successfully recovered from moderate COVID-19 but subsequently developed more severe respiratory failure, which was considered to be a COVID-19-triggered acute exacerbation of idiopathic pulmonary fibrosis (AE-IPF). It is important to be aware of the risk of AE-IPF after COVID-19 and to properly manage this deadly complication of IPF. Recent literature reporting cases with chronic interstitial lung diseases which developed respiratory failure by complications with COVID-19 is also reviewed and discussed.